2019
DOI: 10.24092/crps.2019.090302
|View full text |Cite
|
Sign up to set email alerts
|

Tinospora cordifolia (Giloy) - Therapeutic Uses and Importance: A review

Abstract: Natural products having medicinal value are gaining more importance in clinical research now days due to their better pharmacological response and no side effects as compared to allopathic drugs. Tinospora cordifolia common name is "Guduchi" or "Giloy" is known for its application in the treatment of various diseases in the traditional ayurvedic literature. Active components obtained from the plant and their biological function in disease control has led to active interest in the plant. This review contains ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Anti-diabetic activities are attributed to tannins, cardiac glycosides, flavonoids, saponins, alkaloids such as magnoflorine, palmetine, and jatrorrhizine, and other substances. When rats were given an aqueous extract lacking Tinospora cordifolia extract, glucose levels rose 21.3 percent, insulin levels rose 51.5 percent, triglycerides rose 54.12%, and the glucose insulin index rose 59.8% [4] .…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Anti-diabetic activities are attributed to tannins, cardiac glycosides, flavonoids, saponins, alkaloids such as magnoflorine, palmetine, and jatrorrhizine, and other substances. When rats were given an aqueous extract lacking Tinospora cordifolia extract, glucose levels rose 21.3 percent, insulin levels rose 51.5 percent, triglycerides rose 54.12%, and the glucose insulin index rose 59.8% [4] .…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
“…The active constituents of the giloy plant can be extracted from many portions of the plant, such as the leaves, stems, and roots (Table 1) [4] .…”
Section: Active Constituents Of the Tinospora Cordifoliamentioning
confidence: 99%
See 1 more Smart Citation
“…Protein, Ca, and P content are also moderately high in giloy leaves. [7] Diabetes mellitus is cured by a variety of phytoconstituents which are isolated from various sections of T. cordifolia. Alkaloids, tannins, and cardiac glycosides are some of these phytochemicals.…”
Section: Fig1 Tinospora Cordifolia Leaves and Barkmentioning
confidence: 99%
“…Bioactive compounds of giloy help immune system to fight infections and upholdthe functioning of leucocyte [31]. In a study, cordifolioside A, magnoflorine, β-ecdysone and palmatine were found to be the main phytocompounds in Giloy [32]. Giloy is known for its property that improvesimmunity.…”
Section: Tinospora Cordifoliamentioning
confidence: 99%